A roda de conversa na educação infantil: uma abordagem crítico-colaborativa na produção de conhecimento - Ryckebusch, Claudia Gil (2011)
In general terms, this research aims at analyzing in order to critically understand students and the teacher-researcher s discursive organization in the Chat Circle Activity in a pre-school setting in a private school located in the city of São Paulo. More specifically, it aims at investigating how these participants critically-collaboratively internalize the actions which take part in the collaborative interactions throughout this Activity, and how this internalization affects the process of shared knowledge production. Theoretical framework is based on the Social-Cultural-Historical Activity Theory, as per Vygotsky (1925/2004; 1930/1988; 1934/2001); Leontiev (1977; 1978, 1983) and Engeström (1999a; 1999b; 1999c; 2003); on the concept of dialogism and the discussion of voices as per Bakhtin/Volochinov (1929-30/1988) and Bakhtin (1934-45/1998; 1952-53/1992); in the constructs of collaboration and critical reflection for the joint production of knowledge in the classroom, as discussed by Magalhães (1994; 2004; 2007) and John-Steiner (2002) more specifically focusing on argumentation, as per Pontecorvo (2005), Orsolini (2005); Liberali (2006); De Chiaro and Leitão (2002). The methodology employed that of critical research of collaboration (Magalhães, 1994). The participants involved in this research were the researcher also the teacher of a class of 21 students that took part in the investigation. Data was analyzed following categories developed by Pontecorvo (2005), Orsolini (2005), Bronckart (1999), Koch (1984) and Brookfield & Preskill (2005). Results have revealed that the creation of criticalcollaborative contexts in situations of Chat Circles has promoted transformations in the ways that the students and the teacher-researcher act, thus broadening their possibilities of development and performance in the context itself